Paciente masculino de 2 años de edad con diarrea y gastroenteritis de presunto origen infeccioso. - Acuña Soria, Mirna Patricia (2021)
Gastroenteritis is a pathological process with soft or liquid stools of consistency and more than three stools in 24 hours, with or without the presence of vomiting, or fever, lasting between seven and fourteen days. It causes infectious diarrhea which, according to WHO data, is one of the diseases in children that represents the second cause of morbidity and mortality worldwide. In the present clinical case, a 2-year-old patient with a diagnosis of diarrhea and gastroenteritis of presumed infectious origin is described. Part of the development includes the nutritional evaluation in the infant, review of clinical history, history, eating habits, all these data will allow to know the nutritional diagnosis and intervene adequately to meet the general objective proposed, improving the clinical picture of the patient through a dietotherapeutic plan to avoid associated complications. In conclusion, the objective was achieved, obtaining beneficial and favorable results, avoiding complications associated with diarrhea and gastroenteritis, it was possible to improve the clinical picture of the patient through nutritional treatment by slightly increasing body weight and recovering the hydroelectrolyte balance.